2014
DOI: 10.1371/journal.pone.0093162
|View full text |Cite
|
Sign up to set email alerts
|

Direct T Cell Activation via CD40 Ligand Generates High Avidity CD8+ T Cells Capable of Breaking Immunological Tolerance for the Control of Tumors

Abstract: CD40 and CD40 ligand (CD40L) are costimulatory molecules that play a pivotal role in the proinflammatory immune response. Primarily expressed by activated CD4+ T cells, CD40L binds to CD40 on antigen presenting cells (APCs), thereby inducing APC activation. APCs, in turn, prime cytotoxic T lymphocytes (CTLs). Here, two tumor-associated antigen (TAA) animal models, p53-based and GP100-based, were utilized to examine the ability of CD40-CD40L to improve antigen-specific CTL-mediated antitumor immune responses. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…For these other specificities, resistance to avidity maturation may be epigenetically imprinted, similar to T cell-intrinsic hyporesponsiveness, which makes cells resistant to secondary encounter of antigen (Philip et al, 2017; Schietinger et al, 2012), or may be constrained by regulatory cells distinct from classical Tregs. Studies of T cells in tumor microenvironments that are deemed dysfunctional and of self-specific T cells (Black et al, 2014; Kuball et al, 2009; Malhotra et al, 2016; Moon et al, 2011; Soong et al, 2014; Souders et al, 2007; Wong et al, 2008; Yu et al, 2015) have also revealed that many of these cells are low avidity at the population level, supporting the idea that tolerance, whether spontaneously acquired in the tumor microenvironment or upon self-antigen encounter or, as we show in this study, therapeutically induced by costimulation blockade therapy, may be simultaneously enforced through multiple mechanisms, one of which being the preservation of low-avidity repertoire for the relevant antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these other specificities, resistance to avidity maturation may be epigenetically imprinted, similar to T cell-intrinsic hyporesponsiveness, which makes cells resistant to secondary encounter of antigen (Philip et al, 2017; Schietinger et al, 2012), or may be constrained by regulatory cells distinct from classical Tregs. Studies of T cells in tumor microenvironments that are deemed dysfunctional and of self-specific T cells (Black et al, 2014; Kuball et al, 2009; Malhotra et al, 2016; Moon et al, 2011; Soong et al, 2014; Souders et al, 2007; Wong et al, 2008; Yu et al, 2015) have also revealed that many of these cells are low avidity at the population level, supporting the idea that tolerance, whether spontaneously acquired in the tumor microenvironment or upon self-antigen encounter or, as we show in this study, therapeutically induced by costimulation blockade therapy, may be simultaneously enforced through multiple mechanisms, one of which being the preservation of low-avidity repertoire for the relevant antigen.…”
Section: Discussionmentioning
confidence: 99%
“…There are strong correlations between accumulation of highavidity T cells and clearance of infections (Busch and Pamer, 1999), elimination of tumors (Black et al, 2014; Kuball et al, 2009; Soong et al, 2014), better memory responses (Turner et al, 2008; Zehn et al, 2009), and autoimmunity (Maeda et al, 2014). Low-avidity T cells, however, which are correlated with less effector functionality (Falta et al, 2005; Kuball et al, 2009; Tsang et al, 2011), would be beneficial for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increase in antigen specific CTL cellular immune responses was observed in both p53 and gp100 tumor models. 90 Furthermore, the immune responses were shown to be CD8+ T cell mediated and result in potent antitumor response. The results show that immunostimulatory molecules can be incorporated into DNA vaccines to enhance the vaccines’ potency.…”
Section: Dna Vaccine Design: Circumventing Immune Tolerancementioning
confidence: 99%
“…A growing number of studies, most of which have been performed in mice, suggest that CD40 is functionally expressed also by T cells. The direct T cell stimulatory capacity of CD40 was manifested in a wide range of effects, including differentiation, memory formation, improvement of functional avidity, upregulating antiapoptotic signals and decreasing proapoptotic ones, rescue from exhaustion, and acquisition of resistance to regulatory T cell-mediated suppression (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Yet, other studies failed to confirm these observations (24)(25)(26)(27), and the immunological role played by T cell-expressed CD40 under physiological conditions is still elusive.…”
mentioning
confidence: 99%